The involvement of card game in formal learning approach: accounting card challenge / Muzrifah Mohamed … [et al.] - Mohamed, Muzrifah; Mansor, Siti Mariam; Azizan, Siti Sakinah; Azero, Mohd Afiq (Faculty of Accountancy, 2019)
Drawing from the significance and implications of changes in learning style, this study aims to review the list of theories in tackling issues relating to the learning process of secondary schools ’students. This paper is highly focussed on the learning through play concept where many scholars strongly believe that this concept will drive the students to adequately acquire the knowledge and meet the learning outcomes. This conceptual paper has investigated a formal learning approach through another angle by applying the involvement of game card. This study provides a general overview of the involvement of game card other than conventional teaching based, towards influencing students’ formal learning. This concept paper highlights the contributions of various simulations and tools towards students’ learning in a variety of ways. The theories on game development and students’ involvement will be extensively discussed in this paper to draw the view on how games can optimize students’ learning. As a conclusion, while many students view accounting as a boring subject, it does not need to be one. Instructors need to do more to engage students and prepare them for more innovative and dynamic study environment. By combining traditional teaching methods with student- centered learning (i.e Accounting Card Challenge), an accounting subject can be exciting and enhance student’s involvement.